Clinical features, therapy patterns, outcomes and prognostic factors of solitary plasmacytomas: a report of the Israeli Myeloma Study Group. Issue 14 (6th December 2022) - Ganzel, Chezi; Trestman, Svetlana; Levi, Shai; Gatt, Moshe E.; Lavi, Noa; Vaxman, Iuliana; Rouvio, Ory; Magen, Hila; Lebel, Eyal; Horowitz, Netanel A.; Leiba, Merav; Tadmor, Tamar; et al.
Abstract: Solitary plasmacytoma (SP) is a rare plasma cell dyscrasia. In this retrospective multicenter study, 68 SP patients were included. Compared to solitary extramedullary plasmacytoma (SEP), patients with solitary bone plasmacytoma (SBP) were younger (57.3 vs. 70.9 years, p  = 0.031), had larger plasmacytoma (median: 5.4 vs. 3 cm, p  = 0.007) and higher median involved free light chain level (61 vs. 25.8 mg/L, p  = 0.056). 92.6% of patients were treated by radiotherapy and 11.8% received systemic anti-myeloma treatment. With a median follow-up of 42 months, 45.6% of patients progressed (8.8% – recurrent SP, 36.8% – active myeloma). The median PFS was 58 months and the median OS has not been reached (10-year OS: 84.8%). Patients who received also anti-myeloma treatment had longer PFS compared to those who did not (median not reached vs. 48 months, p  = 0.056). In conclusion, SBP and SEP appear to be different diseases. Radiotherapy is the cornerstone in the SP treatment. A large prospective trial is needed to evaluate the impact of adding systemic anti-myeloma treatment to local radiotherapy.